Prospective Evaluation of Cases of Discharge against Medical Advice in Abuja, Nigeria - Bioku Muftau Jimoh; Obalim-Chris Anthonia; Igwilo Chinwe; Adewumi Oluwafemi; Aremu Ganiyu; Adamu Haroun; Eziechila Chinwe; Aiyekomogbon Joshua (The Scientific World Journal)
Background. Discharge against medical advice (DAMA) is a global clinical phenomenon contributing significantly to adverse patients’ outcome. Literatures abound on self-discharges in specific medical subpopulations. However, multidisciplinary studies on this subject in our region are few. Aim. To prospectively evaluate cases of DAMA in a wholesale multidisciplinary perspective at Federal Staff Medical Centre, Abuja, and suggest strategies to reduce it. Patients and Methods. All consecutive patients who DAMA from our medical centre between June 2013 and May 2014 were included in the study. Data harvested from the standard proforma were analyzed using IBM SPSS version 19.0. Results. We recorded an overall DAMA rate of 2.1%. The majority of the patients were paediatric cases (n=63, 44.6%) while closed long bone fractures represented the leading diagnosis (n=35, 24.8%). The most commonly cited reasons for leaving the hospital were financial constraints (n=46, 32.6%) and seeking alternative therapy (n=25, 17.7%). Conclusion. The DAMA rate in our study is comparable to some urban hospitals elsewhere. However, the leading reasons for this phenomenon are unacceptable in the current medical best practice. Thus, strengthening the Health Insurance Scheme, strict control of traditional medical practices, and focused health education are recommended strategies to reduce DAMA.